Tonic down-rolling and eccentric down-positioning of eyes under sevoflurane anesthesia without non-depolarizing muscle relaxant and its relationship with depth of anesthesia - Chaurasia, Shweta; Soni, Shiv Lal; Ganesh, Venkata; Ram, Jagat; Sukhija, Jaspreet; Chaurasia, Swati; Takkar, Aastha (Frontiers in Medicine, 2023)
Purpose To analyze the relationship between eccentric downward eye movement/eccentric downward eye-positioning (EDEM/EDEP) encountered in patients undergoing ophthalmic surgeries and its return to a centralized position under general anesthesia (GA) with the depth of anesthesia (DOA). Methods Patients undergoing ophthalmic surgeries (6 months-12 years) under sevoflurane anesthesia without non-depolarizing muscle relaxant (NDMR) who witnessed a sudden tonic EDEM/EDEP were both retrospectively (R-group) and prospectively (P-group) enrolled (ambispective study). R-group included data-points after induction (AI) till the time surgery lasted while P-group compiled data both during induction (DI) and AI. DOA in terms of MAC (minimum alveolar concentration) at the time of EDEM/EDEP and centralization of eyeball and their timings were noted and compared for both AI and DI data-points. Also, vertical eccentric eye positions were scored and correlated with MAC. Results AI data included 22 (14R+8P) events and their mean MAC of EDEM/EDEP and centralization were 1.60 ± 0.25 and 1.18 ± 0.17 respectively (p = 0.000). DI data included 62 (P) cases and its mean MAC of EDEM/EDEP and centralization was 2.19 ± 0.43 and 1.39 ± 0.26 respectively (p = 0.000). Median (IQR) eye positions during down-positioning in 84 events was −3 (−3.9 to −2.5). It was preceded by an eccentric upward drift of eyes in 10/22 (6R+4P) AI cases. A strong negative correlation was seen between DOA and eccentric eye positions (r = −0.77, p = 0.000). Conclusions Tonic down-rolling of eyes is not uncommon in children seen without NDMR with higher depths of sevoflurane anesthesia compared to point of centralization and fluctuations in DOA should be avoided to circumvent inadvertent complications during ocular surgery.